2022
DOI: 10.24235/sc.educatia.v11i1.10278
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of LabXChange as a Virtual Laboratory Media to Improve Digital and Information Literacy for Biology Education Undergraduate Students

Abstract: Learning media is very important in order to facilitate learning or the income of information. In this 21st century, learning is not only focused on how to get but also how to find. 21st-century learning is also emphasized on digital literacy and also information literacy which is considered a fast door to learning. High digital literacy and information literacy, will facilitate the learning process carried out by students. This study aims to determine whether using LabXChange can improve or facilitate subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results showed that the Titration Screen Experiment affected students' digital literacy. These findings agreed with a prior study by Alt and Raichel (2020) and Listiawati et al (2022). They found that digital media, such as virtual labs, can significantly affect digital literacy.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that the Titration Screen Experiment affected students' digital literacy. These findings agreed with a prior study by Alt and Raichel (2020) and Listiawati et al (2022). They found that digital media, such as virtual labs, can significantly affect digital literacy.…”
Section: Resultssupporting
confidence: 92%
“…Virtual laboratories are oriented on how students' skills are facilitated through virtual laboratory activities and how students know and understand what they do in authentic contexts. To support an all-digital virtual laboratory, students require a deeper understanding of digital literacy, including existing features (Listiawati et al, 2022). Figure 3 shows that students had quizzes before experimenting in the Titration Screen Experiment.…”
Section: Paper | 86mentioning
confidence: 99%
“…for the SW of PoC19S get a result of 0.067, where with a confidence level (α) 0.05, then all normality results from the data used are to get an interpretation of Sig. > α, which indicates that all data are normal so that the data used can absolutely be tested for the hypothesis using the independent sample ttest, but before doing the hypothesis test, a homogeneity test was carried out, even though Listiawati (2022) states that the homogeneity test is not an absolute requirement, but this study uses two populations with different numbers of subjects and different timeframes, so a homogeneity test should be carried out because it ensures the validity of the data used (Nam, 2017). Following are the results of the homogeneity test using the Levene Test which can be seen in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…In its implementation, online learning activities during Covid-19 had many innovations in the use of appropriate technology, to the development of new learning models. Focusing on innovation, various innovations to facilitate online learning have been carried out, such as using the WhatsApp application to facilitate the learning process (Susilawati & Supriyatno, 2020), using interactive LMS applications such as LabXChange for laboratory activities (Listiawati et al, 2022), up to developing e-books as teaching materials for the Covid-19 pandemic (Malaquias et al, 2021). Focusing on developing learning models, there is one learning model that was born in the Covid-19 era, namely the Sophisticated Thinking Blended Laboratory (Agustina & Putra, 2022) where the model combines two real and real laboratory activities, and the implementation of real laboratory activities can be designed to work remotely (remote laboratory).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory activity applies experiments intending to find the truth and/or verify a theory (Listiawati et al, 2022). Laboratory activities in learning should include the ability to improve students.…”
Section: Introductionmentioning
confidence: 99%